Sustainable Acid Mine Drainage Water Reclamation Using Silica-pectin Multichannel Tubular Membrane: A Comparison of Ultrafiltration Vs Pervaporation - Zaki, Dhimas Ekky Zaghlul; Aliyanti, Alya Dita; Kusumawati, Uun; Pratama, Reza Satria Kelik; Rahma, Aulia; Mustalifah, Fitri Ria; Mahmud, Mahmud; Elma, Muthia (Heca Sentra Analitika, 2024)
The practice of coal mining has been demonstrated to exert a detrimental impact on the surrounding environment, particularly through the formation of acid mine drainage (AMD) ponds, which have the potential to pollute water sources. The reclamation of AMD is necessary to treat wastewater to ensure its safety for discharge into the environment and subsequent use as clean water. This study aims to treat AMD by comparing ultrafiltration (UF) and pervaporation (PV) processes utilizing silica-pectin multichannel membranes. The membranes were fabricated by coating silica-pectin sol on an inner surface of multichannel tubular support. The UF process was conducted under various pressures (1-3 bar), while the PV process was tested at various feed temperatures. Both permeate were collected and analyzed using several parameters (pH, Mn, and conductivity). The results showed that the UF process is more effective in collecting permeate flux over 136.6 L.h-1.m-2 at 3 bar pressure. Meanwhile, PV performs high permeate quality with Mn and conductivity rejection of 99.9 and 96.5%, respectively. Both UF and PV processes exhibit slightly increasing permeate pH with a range of 4.5-5.6. It concluded that multichannel silica-pectin membranes successfully reclamation AMD to enhance water quality. In addition, the UF process is more affordable for recycling AMD with high permeate flux, pretty good Mn, and conductivity rejection of over 95%.